A Case study on Pan Magic Food Center - Dalmacio, Rhoda; Duero, Emmanuel; Estanislao, Roderico; Quinzon, Judith (Quezon City UP College of Engineering, 1991)
A case study presented basically deals about eating ,one of life's most pleasurable , and satisfying activities.Such broad activity has been limited to a single and brief dimension,the cafeteria.Basically,the study center on Pan Magic Food Center between Yakal and Ipil Residence Halls behind the College of Engineering.It deals with its inadequate attraction and maintenance of customers.This study endeavours to bring enough information and solution to this existing situation.And hopefully,it can prevent to the readers an alternative eating place given the present food service problem in their locality.The study involves a limited number of population which was chosen due to their proximity to Pan Magic.The extent of study is further limited by the cost and expenses and a number of assumptions.The study which was carried out through interviews,surveys,backed by literature reading show that primarily,Pan Magic Has problems with its promotion and lay-out.Given the solution to these major,as well as minor,problems Pan Magic can be an alternative eating place.
Feasibility study.
Submitted in partial fulfillment of the course requirements in IE 3: Introduction to Industrial Engineering
Keywords: Cafeterias -- Philippines; Universities and colleges -- Food service -- Philippines; Universities and colleges -- Food service -- Philippines -- Evaluation; Universities and colleges -- Food service -- Philippines -- Quality control